Study of Magnetic and Electrical Property for Different Types of Prepared Mesogenic Organo – Semiconductors - O. Mousa Al-Uqaily, Abdulazeez; K. H. Al-khalaf, Alaa; J. Abdul-razzaq, Shaymaa; M. Sh. Al-jomali*, Qaiss (Al-Qadisiyah Journal of Pure Science, 2018)
Synthesis and characterization were achieved for three mesogenic complexes of Schiff’s base (mesogenic legand) with ions of (Cu+2, Co+2, and Mn+2) as the following structure: The legand and their complexes have been characterized by a spectrophotometer Infrared (IR), Ultra violet (UV), polarizing microscope equipped with heating stage, and Differential scanning calorimeter (DSC), techniques were found to be nematic (enantiotropic). The magnetic sensitivity of these compounds has been investigated. Molar conductivity for the legand have shown that the free liquid crystal compound (twin dimmer) is non electrolyte solution while their complexes are electrolyte, that means the negative ions are swimming out of coordinated ball, as the following: [DBB-MnII].Cln.X; [DBB-CuII].Cln.X; [DBB-CoII].Cln.X The legand effect of complexation with (Cu+2, Co+2, and Mn+2) on the (D.C) and (A.C) values have been clear when the (D.C) electrical conductivity ranged from (10-12) to (10-9) (ohm.cm)-1 lies in the usual range of organic semiconductors.14,15 The (A.C) electrical conductivity increases in the range of (10-11) to (10-6) (ohm.cm)-1. However, the measurements of magnetic sensitivity for the complexes are refer to have a paramagnetic property and have single electrons in outer electronic levels of the metal atoms, these compounds have the following trend: (DBB-Mn +2) > (DBB- Cu +2) > (DBB-Co+2). Key words: Schiff’s base, magnetic sensitivity, semiconductors.